Rethinking Educational Practice Through Reflexive Inquiry
XX, 260 p.
Keywords: Susan Groundwater-Smith is one of the most influential voices in the world of educational practitioner inquiry. The convener in Australia of the Coalition of Knowledge Building Schools, she is a staunch advocate of innovative methods of practitioner inquiry with a particular emphasis upon student voice and the use of images in capturing young people’s perspectives on their learning experience. So it is more than fitting that this unique text on practitioner inquiry and teacher professional learning is dedicated to her. Rethinking Education Practice Through Reflexive Inquiry is a compilation of essays that explore contemporary issues in practitioner inquiry and action research from the perspective of both university-based and school-based authors. The essays discuss the practical, political and theoretical dimensions of practitioner inquiry, advancing the argument that the adoption of an inquiring approach to practice is both an integral dimension of teachers’ work in the modern school as well as critical to effective and authentic professional learning. And the essays draw on the work of Groundwater-Smith to demonstrate the benefits brought to bear on schools, teachers and learners when the complex nature of the relationship between inquiry and practice is understood and acted upon in pursuit of democratic knowledge interests.